2022
DOI: 10.3390/jcm12010206
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Analysis of Motor and Neuropsychiatric Symptoms in Patients with Huntington’s Disease from China: A Cross-Sectional Study

Abstract: Huntington’s disease (HD) is an autosomal dominant inherited neurodegenerative disorder caused by CAG repeats expansion. There is a paucity of comprehensive clinical analysis in Chinese HD patients due to the low prevalence of HD in Asia. We aimed to comprehensively describe the motor, neuropsychiatric symptoms, and functional assessment in patients with HD from China. A total of 205 HD patients were assessed by the Unified Huntington’s Disease Rating Scale (UHDRS), the short version of Problem-Behavior Assess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In this study, 92 individuals with gene-confirmed HD were recruited between March 2009 and November 2023 in the Department of Neurology at West China Hospital of Sichuan University (Chengdu, China). The participants in this study were from the same cohort as the previous study ( 3 , 26 ). The study received approval from the Institutional Ethics Committee of West China Hospital, Sichuan University, China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 92 individuals with gene-confirmed HD were recruited between March 2009 and November 2023 in the Department of Neurology at West China Hospital of Sichuan University (Chengdu, China). The participants in this study were from the same cohort as the previous study ( 3 , 26 ). The study received approval from the Institutional Ethics Committee of West China Hospital, Sichuan University, China.…”
Section: Methodsmentioning
confidence: 99%
“…An abnormal amplification of CAG causes HD repeats in exon 1 of the Huntingtin ( HTT ) gene, located on chromosome 4 ( 1 ). It usually begins to manifest in mid-adulthood and lasts for about 15–20 years ( 2 , 3 ). To date, there are no effective disease-modifying therapies, imposing a heavy economic burden on families and society which increases as the disease progresses ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The UHDRS–total motor score (TMS) and the total functional capacity (TFC) score (Shoulson et al., 1989) were used to assess the motor symptom and to quantify a patient's ability to perform basic and instrumental activities of daily living as described previously (Cheng et al., 2022). Participants were divided into two groups, which were sever motor symptom (TMS score more than mean score) and mild motor symptom (TMS score less than mean score).…”
Section: Methodsmentioning
confidence: 99%
“…from the Department of Neurology of West China Hospital. The participants of this study was based on the same cohort as the previous study (Cheng et al, 2022).…”
Section: Participantsmentioning
confidence: 99%
“…HD gene carriers could remain unnoticed for several years before receiving a diagnosis. [ 8 ] Disease manifestations could begin at any time in life, although the majority of cases display evident onset in middle age. The length of the CAG repeats accounts for about 50%–70% of the overall variance in age of onset.…”
Section: Introductionmentioning
confidence: 99%